(+)-Kunstlerone, a New Antioxidant Neolignan from the Leaves of Beilschmiedia kunstleri Gamble - Mollataghi, A.; Hadi, A.H.; Awang, K.; Mohamad, J.; Litaudon, M.; Mukhtar, M.R. (MDPI, 2011)
A new neolignan, 3,4-dimethoxy-3',4'-methylenedioxy-2,9-epoxy-6,7-cyclo-1,8-neolign-11-en-5(5H)-one, which has been named (+)-kunstlerone (1), together with six known alkaloids: (+)-norboldine (2), (+)-N-methylisococlaurine (3), (+)-cassythicine (4), (+)-laurotetanine (5), (+)-boldine (6) and (-)-pallidine (7), were isolated from the leaves of Beilschmiedia kunstleri. The structures were established through various spectroscopic methods notably 1D- and 2D-NMR, UV, IR and LCMS-IT-TOF. (+)- Kunstlerone (1) showed a strong antioxidant activity, with an SC(50) of 20.0 µg/mL.